The low seroprevalence of tick-transmitted agents of disease in dogs from southern Ontario and Quebec - Gary, Anthony T. (Canadian Veterinary Medical Association, 2006)
Infectious diseases caused by pathogens transmitted by ticks and other insect vectors are an important cause of morbidity and mortality in both dogs and humans throughout North America. The purpose of this study was to determine the seroprevalence of selected vector-transmitted pathogens in southern Ontario and Quebec. Samples submitted to the Vector Borne Disease Diagnostic Laboratory (VBDDL) at the North Carolina State University College of Veterinary Medicine were evaluated for antibodies to Ehrlichia canis, Anaplasma phagocytophilum, Babesia canis, Bartonella henselae, Borrelia burgdorferi, Bartonella vinsonii subspecies berkhoffii, and Rickettsia rickettsii. Information regarding breed and the city or province from which the sample originated was recorded; however, travel history was unknown for the majority of dogs. Overall seroprevalence to these tick-borne pathogens in southern Ontario and Quebec is low compared with most regions of the United States, suggesting that veterinarians in this region of Canada should pursue diagnostic evidence of infection in dogs with a travel history or prior residence in areas endemic for exposure to tick-borne infections.